CORRELATION OF ALKALOID CONTENT AND TASTE OF HONEY FROM VARIOUS PROVINCES IN INDONESIA - MAHANI, M.; WULANDARI, E.; LEMBONG, E.; ADELA, L. H. R. (International Journal of Pharmacy and Pharmaceutical Sciences, 2022)
Objective: This study analyzed the correlation between alkaloid contents and taste (bitter and rough taste). Methods: Qualitative analysis was analyzed using Mayer and Draggendorff methods, while quantitative analysis was analyzed using spectrophotometric methods. Taste evaluation in each sample was carried out by descriptive method with parameters including bitter and rough taste. The correlation between alkaloid content and taste in honey was statistically analyzed using a correlation test. Results: The alkaloids testing showed that the sample with the highest alkaloid content was Tetragonula fuscobalteata honey from Sumbawa province, with an alkaloid content of 119.71 mg/g. In contrast, the sample with the lowest alkaloid content was Geniotrigona thoracica from West Sumatra at 21.24 mg/g. Taste evaluation results showed that the sample with the highest alkaloid content had the most bitter and rough taste. Conclusion: Honey that has the highest alkaloid content is T. fuscobalteata Sumbawa, with an alkaloid content of 119.71 mg/g, because the availability of adequate alkaloid feed supports this species. In contrast, the honey with the lowest alkaloid content was G. thorasica, with an alkaloid content of 21.24 mg/g, because the availability of adequate alkaloid feed did not support this species. Based on the data, the alkaloid content of honey has a linear correlation with the bitter and rough taste. The higher alkaloid content in honey causes the honey taste to become more bitter and rough.